TEACHER ORIENTATION TO PROMOTE SELF STUDY ON THE ACTIVITY WITH THE USE OF THE TEXTBOOK IN MATH CLASS - Almeida Carazo, Bernardino A.; Salcedo Estrada, Inés (Atenas, 2014)
The article highlights the actions taken by the researchers of the UCP "Juan Marinello Vidaurreta" of Matanzas, in the project "The Individual and group counseling for the development of basic secondary educational work according to the study activity" aimed at diagnosing , visit classes, train principals and teachers, and develop individual queries. They have helped improve the preparation of teachers to promote self-regulation in the activity of study with the use of the textbook in math class.